Christian economic ethics : history and implications - Finn, Daniel K., 1947- (Fortress Press, 2013)
What does the history of Christian views of economic life mean for economic life in the twenty-first century? Here Daniel Finn reviews the insights provided by a large number of texts, from the Bible and the early church, to the Middle Ages and the Protestant Reformation, to treatments of the subject in the last century. Relying on both social science and theology, Finn then turns to the implications of this history for economic life today. Throughout, the book invites the reader to engage the sources and to develop an answer to the volume's basic question.